Legal issues in the digital economy the impact of disruptive technologies in the labour market - Filì, Valeria; Costantini, Federico (ADAPT labour studies book-series., 2019)
It is a matter of fact that technological innovation is deeply impacting on our culture, society, economy and labour market. The massive and widespread use of Artificial Intelligence and the strengthening of the collaborative economy (also known as 'gig' or 'platform' economy) are blurring the traditional legal categories and creating new requirements for protection for employed and self-employed workers. This book represents a tool to understand where we are and where we are going, focusing on old and new legal categories and labour market policies. The chapters included in this volume cover.